ASAP ROKOK KONVENSIONAL DAN ELEKTRONIK MEMBERIKAN GAMBARAN KERUSAKAN STRUKTUR ALVEOLUS YANG SAMA - Jenny Lauvita; Tena Djuartina; Dyonesia Ary; Iskandar Rahardjo Budianto; Robi Irawan (Atma Jaya Catholic University of Indonesia, 2022)
Introduction: Cigarettes have become the cause of health problems and even death, especially in developing countries like Indonesia. Cigarettes contain various free radical components for the body, thereby increasing inflammation in various organs and tissues, especially the lungs. This will trigger proteolysis so that the alveoli lose elasticity. Electronic cigarettes are then introduced as an alternative to reduce smoking. However, there has been not enough research conducted on their safety and long-term effects of e-cigarettes, so researcher aim to compare the impact of conventional and electronic cigarettes on alveolar damage. Methods: This research was conducted experimentally, using 30 male Sprague Dawley rats aged 10-12 weeks and weighing 150-250 grams as sample. These rats were necropsed after being exposed to cigarettes smoke and e-cigarettes vapor for 2 weeks and 4 weeks to make lung tissue preparations with HE staining. These preparations were observed under a microscope to measure the degree of alveolar damage based on the edema, alveolar septal destruction, and inflammatory cell infiltration. Finally, the data was analyzed using Kruskal-Wallis followed by one-Mann-Whitney statistical tests with STATA. Results: Rats exposed to conventional cigarette smoke and e-cigarette vapor in the second week already showed significant alveolar damage compared to the control group. (p<0.05). However, there was no significant difference between exposure for 2 weeks and 4 weeks. (p>0.05) Between rats given conventional cigarette smoke and electronic cigarette vapor, there was no significant difference in degree of alveolar damage at week 2 and week 4. (p>0.05) Discussion: As a result, both conventional cigarette smoke and e-cigarette vapor have the same effect on alveolar damage. This is because both conventional cigarette smoke and e-cigarette vapor contain nicotine which will trigger the release of fibronectin so that it can trigger fibrosis in the lung parenchyma. In addition, the carbon monoxide contained in both can inhibit fibroblast proliferation and damage the elastin in the alveolar wall, so that the alveoli lose its elasticity and tend to expand. Keywords: Lung inflammation, cigarettes effect on lungs, e-cigarettes, tobacco cigarette, lung damage